Beyond contestation: conceptualizing negotiation in democracy promotion. Issue 5 (4th July 2019) - Poppe, Annika Elena; Leininger, Julia; Wolff, Jonas
ABSTRACT: This article presents an analytical framework that guides the contributions to this special issue and, in general terms, aims at enabling a systematic investigation of processes of negotiation in the international promotion of democracy. It first briefly introduces the rationale for studying democracy promotion negotiation, offers a definition, and locates the general approach within the academic literature, bringing together different strands of research, namely studies of negotiation in international relations as well as research on democratization and democracy promotion. The larger part of the article then discusses key concepts, analytical distinctions and theoretical propositions along the lines of the three research questions that are identified in the introduction to this special issue. More specifically, the article (1) offers a typology that facilitates a systematic empirical analysis of the issues that are discussed in democracy promotion negotiations; (2) takes initial steps towards a causal theory of democracy promotion negotiation by identifying and discussing a set of parameters that can be expected to shape such negotiations; and (3) introduces key distinctions and dimensions that help guide empirical research on the output and outcome of negotiations in democracy promotion.